Mediumistic Materializations in France During the Early 1920s: A Review of Recent Works - Alvarado, Carlos S. (Journal of Scientific Exploration, 2021)
As I have argued before in this journal, there is a rich tradition of psychical research studies of materialization mediums published before 1930 (Alvarado, 2019a). The phenomenon, associated with many well-known mediums such as Eva C., Florence Cook, William Eglinton, D. D. Home, Franek Kluski, and Eusapia Palladino, has been reviewed by many both during the nineteenth century and later (e.g., Moses, 1884–1886; Richet, 1922, Part 3). Opinions about it have been diverse. In a review of nineteenth-century evidence about it in his book Modern Spiritualism, Frank Podmore (1902, Vol. 2, Chapter 6) was rather dubious about the existence of the phenomenon. In his later concise history of psychical research, Rudolf Tischner (1924) argued that we cannot be sure if “strict proof of the reality of materialization has been provided,” but there has been “circumstantial evidence of considerable strength” (p. 68; this, and other translations, are mine). More positively, Charles Richet (1922) wrote in his celebrated Traité de métapsychique that materializations could “take a definitive rank in science” even if “we understand absolutely nothing about it” (p. 690). Over the years these attitudes have been maintained by many writers and students of the subject, some of which speculate about vital forces and spirit action. In addition, there have been various reports of fraud with materialization mediums (e.g., Sitwell & Von Buch, 1880; Wallace, 1906). Students of the history of materialization phenomena are aware of the studies on the subject by French individuals such as Juliette Bisson and Gustave Geley. This is the main work reviewed by Antonio Leon, who has a doctorate in history from the Federal University of Rio de Janeiro. In Sessões de Ectoplasmia, which focuses on French developments during the 1920s, Leon analyzes materialization phenomena, some of which were studied at the Institut Métapsychique International (IMI) during the 1920s. This book appears at an appropriate time because IMI celebrated their centenary in 2019. Leon states that in his work about IMI he set out to investigate how the experiments took place, their organization, the precautions taken to prevent fraud, their procedures of control, the phenomena, their description, and who the mediums were and the investigators involved . . . [The book] aims to verify the various aspects that pervaded the experiments during the decade of the 1920s, . . . the values and rules of the investigations of ectoplasm of this period. It will also focus on the research context in which the experiments were located. (p. 19)